Difficulties and possibilities in communication between referring clinicians and radiologists: perspective of clinicians - Fatahi, Nabi (J Multidiscip Healthc, 2019)
PURPOSE: To investigate modes and quality of interprofessional communication between clinicians and radiologists, and to identify difficulties and possibilities in this context, as experienced by referring clinicians. PATIENTS AND METHODS: Focus group interviews with 22 clinicians from different specialties were carried out. The leading question was: "How do you experience communication, verbal and nonverbal, between referring clinicians and radiologists?" Content analysis was used for interpretation of data. RESULTS: Overall, referring clinicians expressed satisfaction with their interprofessional communication with radiologists, and digital access to image data was highly appreciated. However, increased reliance on digital communication has led to reduced face-to-face contacts between clinicians and radiologists. This seems to constitute a potential threat to bilateral feedback, joint educational opportunities, and interprofessional development. Cumbersome medical information software systems, time constraints, shortage of staff, reliance on teleradiology, and lack of uniform format of radiology reports were mentioned as problematic. Further implementation of structured reporting was considered beneficial. CONCLUSION: Deepened face-to-face contacts between clinicians and radiologists were considered prerequisites for mutual understanding, deepened competence and mutual trust; a key factor in interprofessional communication. Clinicians and radiologists should come together in order to secure bilateral feedback and obtain deepened knowledge of the specific needs of subspecialized clinicians.